Synthesis and properties rhenium complex with nbutanol and i-butanol. - O. V. Petrakova (Тонкие химические технологии, 2009)
First rhenium oxobutoxoderivatives with n-BuOH and i-BuOH have been obtained by electrochemical method. The decomposition rhenium complex with n-BuOH at 412°С in oxidizing atmosphere results in obtaining oxides of Re(VI) and Re(IV) in the condensed phase.